Improving the Efficiency of Public Authorities - PROKOFIEV, Stanislav E.; PANINA, Olga V.; EREMIN, Sergey G.; GALKIN, Andrey I.; KOMOV, Valeriy J. (Journal of Advanced Research in Law and Economics; Vol 10 No 6 (2019): JARLE Volume X Issue 6(44) Fall 2019, 2019)
The article analyzes one of the most advanced regulatory documents in the field of state budgeting, namely: The concept of increasing the efficiency of budget expenditures in 2019–2024. Significant, according to the authors, measures to improve the efficiency of public authorities, which are listed in the reviewed Concept, are highlighted. These measures are divided into two lists. The first list contains measures that are more general in nature, the second one is more specific. The Russian Federation is actively implementing the principles of project management and is making the transition to program budgeting. In this regard, one of the main ways to assess the effectiveness of state bodies is to assess the effectiveness of the implementation of state programs. Significant shortcomings of the methods of evaluation of state programs, identified by the results of the analysis conducted by a number of authors, are described. The article provides a definition of efficiency in accordance with the Budget Code of the Russian Federation. The authors' point of view on the effectiveness of the work of state bodies is presented. The following aspects of this concept are considered: social efficiency, efficiency of the organization of management, efficiency of the functioning of the management system. The meritocratic tendencies are mentioned in the selection of civil servants in the Russian Federation. As a result of the study, an algorithm was proposed for increasing the efficiency of public authorities, which reflects the effect of specific measures on the considered aspects of efficiency.